1998
DOI: 10.1038/3833
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic imprinting is disrupted in interspecific Peromyscus hybrids

Abstract: Genomic imprinting, the unequal expression of gene alleles on the basis of parent of origin, is a major exception to mendelian laws of inheritance. By maintaining one allele of a gene in a silent state, imprinted genes discard the advantages of diploidy, and for this reason the rationale for the evolution of imprinting has been debated. One explanation is the parent-offspring conflict model, which proposes that imprinting arose in polyandrous mammals as the result of a parental conflict over the allocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 27 publications
3
151
1
Order By: Relevance
“…Also, Igf 2 is an imprinted gene, and it has been shown recently that imprinting may be disrupted in interspecific Peromyscus hybrids (Vrana et al, 1998). When we compared Igf 2 expression in X Msp and X Mmu placentas, two differences were seen.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, Igf 2 is an imprinted gene, and it has been shown recently that imprinting may be disrupted in interspecific Peromyscus hybrids (Vrana et al, 1998). When we compared Igf 2 expression in X Msp and X Mmu placentas, two differences were seen.…”
Section: Discussionmentioning
confidence: 90%
“…However, recently it was suggested that in the placental hybrid dysgenesis effects described in Peromyscus, autosomal imprinted genes may play a major role (Vrana et al, 1998(Vrana et al, , 2000. An autosomal imprinted gene which has been shown to be pivotal in control of placental growth is Igf 2 (Baker et al, 1993;Lopez et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the trans-acting machinery that regulates imprinting, such as DNA methyltransferase deficiency (Lei et al, 1996;Bourc'his et al, 2001;Hata et al, 2002;Kaneda et al, 2004;Arima et al, 2006) or mutations causing familial hydatidiform moles (Judson et al, 2002;Murdoch et al, 2006) result in abnormal placentation. Finally, interspecific hybrids (Vrana et al, 1998;Vrana et al, 2000), somatic cell nuclear transfer embryos (Dindot et al, 2004;Inoue et al, 2002) and uniparental embryos (Surani et al, 1986;Varmuza et al, 1993;Mann 2005) all suffer from dysmorphic trophoblast, in part or in whole because of abnormal expression of imprinted genes.…”
Section: Sfmbt2 and Yy1 Interact In Mammalian Cellsmentioning
confidence: 99%
“…Disruption of imprinting in interspecific mammalian hybrids of the deermouse, Peromyscus maniculatus, may be due to nuclearcytoplasmic incompatibility 48 . Furthermore, certain oocyte cytoplasmic modifiers can induce epigenetic modifications of target loci, subsequently rendering them inactive by DNA methylation 49 .…”
Section: Genomic Reprogramming In the Zygotementioning
confidence: 99%